Elaboration on Production of Idioms and Idiomatic Expressions by ESL Learners - Harun Bastug; Selma Salıhagıc (Sakarya University Journal of Education)
Learning a language implies learning both, its literal and figurative elements. Idioms, as figurative expressions in language, are considered as very important part of communication, since they are commonly and very often used in English language in speaking and writing, as well as in formal and informal context. The aim of this paper is to present results of a study which purpose is aimed to investigate whether there is a correlation between idioms knowledge and idioms production. The study is conducted at International Burch University on the multicultural students of English Language and Literature Department on the assumption that even if learners of ESL are being taught and exposed to hear idioms, understand them and are aware of their importance, still, they are reserved when it comes to their usage in communication. Answers have been sought on the following research questions: Can students recognize idioms? Do students understand idioms? Do students use idioms in their communication? We have seen that participants despite their awareness don’t use as much idioms while communicating, speaking or writing which all require productive language skills. It may be the result of lack of exposure to English in its cultural environment.